Rectificacion de aceros fragiles y ductiles: Parametros de entrada para obtener los mejores resultados - Bianchi, E. C.; Aguiar, P. R.; Monici, R. D.; Silva, E. J. (My University, 2002)
In this work, the behavior of the steel surface grinding process with conventional grinding wheels was studied for various grinding conditions and a fixed dressing condition. The input parameters (wheel speed, workpiece speed, depth of cut), that set up the grinding conditions were determined as a function of the characteristics of the grinding machine. A test bench was established where the grinding power was measured in real time as a function of the volume of material removed. The results showed that in the grinding of fragile steels with a soft wheel and medium grit size, the average power of the cut shows a tendency to increase and become stabilized. The surface roughness of the piece decreased in all the tests and was proportional to the increase in the number of active grits. In tests on the grinding of ductile steels with a soft wheel and fine grit size, the wheel became dull until the moment that the abrasive grits were released from the cut surface.
Grinding of brittle and ductile steels: Input parameters required to obtain optimal results
Keywords: Grinding; Grinding forces; Grit size; Machining conditions; Rugosity; Brittleness; Ductility; Grinding (machining); Grinding wheels; Surface roughness; Test facilities; Fragile steels; Steel testing